2014
DOI: 10.1371/journal.pone.0084523
|View full text |Cite|
|
Sign up to set email alerts
|

Differentially Expressed Genes in Bordetella pertussis Strains Belonging to a Lineage Which Recently Spread Globally

Abstract: Pertussis is a highly contagious, acute respiratory disease in humans caused by the Gram-negative pathogen Bordetella pertussis. Pertussis has resurged in the face of intensive vaccination and this has coincided with the emergence of strains carrying a particular allele for the pertussis toxin promoter, ptxP3, which is associated with higher levels of pertussis toxin (Ptx) production. Within 10 to 20 years, ptxP3 strains have nearly completely replaced the previously dominant ptxP1 strains resulting in a world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 77 publications
3
70
0
2
Order By: Relevance
“…Although the ptxP3 allele is thought to increase pertussis toxin expression (40,41), a recent comparison of isogenic mutants found that the ptxP3 allele and the genetic background, which includes genomic structure, independently enhance colonization in mice (42). Similarly, although alleles of fimH contain polymorphisms in the predicted surface epitope region, differences in immune recognition remain untested (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ptxP3 allele is thought to increase pertussis toxin expression (40,41), a recent comparison of isogenic mutants found that the ptxP3 allele and the genetic background, which includes genomic structure, independently enhance colonization in mice (42). Similarly, although alleles of fimH contain polymorphisms in the predicted surface epitope region, differences in immune recognition remain untested (43).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies not yet confirmed hypothesized the possible overexpression of virulence factors such as PT or differential gene expression regulation of nonvaccine-type isolates harboring the ptxP3 allele [65]. Genetic expression is however highly dependent on growth conditions such as the medium used, and these results are hard to reproduce.…”
Section: The B Pertussis Los Endotoxinmentioning
confidence: 99%
“…This is unfortunate, as strains are required for more in-depth analyses, such as whole-genome sequencing, transcriptomics, and proteomics (44)(45)(46)(47). A convenient way to obtain isolates, without compromising PCR, is to streak a nasopharyngeal swab on selective media after elution of the swab with water or physiological salt for PCR.…”
Section: Culturementioning
confidence: 99%